Purification of memory : a study of modern Orthodox theologians from a Catholic perspective - Mong, Ambrose Ih-Ren, 1959- (Cambridge : James Clarke & Co., 2015)
Among the major Christian denominations, the Orthodox Church is the least known and widely misunderstood. This is more serious in Asia where the Orthodox Church is a minority and is perceived as an exotic branch of Christianity. But in fact, the Eastern Church has been in China since the seventeenth century. The purpose of this work is to acquaint lay people, theological students and seminarians with the teaching of Orthodoxy through a study of important modern Orthodox theologians. Mong argues that in spite of the differences and painful clashes between the Eastern and Western Churches, there.
Front Cover; Title Page; Copyright Information; Dedication; Contents; Foreword; Preface; Introduction; Chapter 1. John Meyendorff; Chapter 2. Nicholas Afanasiev; Chapter 3. John Zizioulas; Chapter 4. Georges Florovsky; Chapter 5. Sergius Bulgakov; Chapter 6. Vladimir Lossky; Chapter 7. Nicolas Berdyaev; Chapter 8. Jaroslav Pelikan; Conclusion; Bibliography; Back Cover
Online resource; title from PDF title page (Ebsco, viewed July 2 2015).
Includes bibliographical references.
Keywords: Theologians; Catholic Church -- Doctrines; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Orthodox Eastern Church -- Doctrines; Orthodox Eastern Church -- Liturgy; Spirituality -- Orthodox Eastern Church; Catholic Church; Theologians; Theology, Doctrinal; RELIGION / Christian Theology / General; Electronic books